Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC

GASEOUS EXCHANGES AND THEIR REGULATION IN 2 SPECIES OF EVERGREEN OAK (QUERCUS ILEX AND QUERCUS SUBER) - VIGNES, D (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1988)
This article presents a comparison on the physiology (hyrdic potential, stomatal resistances, transpiration, net photosynthesis) of young plants of Quercus ilex and Quercus suber submitted to different temperatures, light environment and water supply. Relative to temperature and light, the two species present similar reactions, although gaseous exchanges are more important on Quercus ilex. On the contrary, they present distinctive differences on water absorption. Quercus ilex have an important transpiration when water supply is not limited, but presents also a good tolerance to low hydric potentials and sufficient stomatal conductance according to photosynthetic production. On Quercus suber, survival seems more important than production : water consumption is relatively reduced at high water potential as good as at low water potential.
APS
Keywords: hydric potential; photosynthetic production; Plant physiology; Quercus ilex; Quercus suber; Stomatal conductance